Essential Role of CFAP53 in Sperm Flagellum Biogenesis - Wu, Bingbing; Yu, Xiaochen; Liu, Chao; Wang, Lina; Huang, Tao; Lu, Gang; Chen, Zi-Jiang; Li, Wei; Liu, Hongbin (Frontiers in Cell and Developmental Biology, 2021)
The sperm flagellum is essential for male fertility. Despite vigorous research progress towards understanding the pathogenesis of flagellum-related diseases, much remains unknown about the mechanisms underlying the flagellum biogenesis itself. Here, we show that the cilia and flagella associated protein 53 (Cfap53) gene is predominantly expressed in testes, and it is essential for sperm flagellum biogenesis. The knockout of this gene resulted in complete infertility in male mice but not in the females. CFAP53 localized to the manchette and sperm tail during spermiogenesis, the knockout of this gene impaired flagellum biogenesis. Furthermore, we identified two manchette and sperm tail-associated proteins that interacted with CFAP53 during spermiogenesis. The disruption of Cfap53 decreased the expression level of these two proteins and disrupted their localization in spermatids. Together, our results suggest that CFAP53 is an essential protein for sperm flagellum biogenesis, and its mutations might be associated with MMAF.